2006
DOI: 10.1242/jeb.02036
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensitivities of cytosolic malate dehydrogenases from native and invasive species of marine mussels (genusMytilus):sequence-function linkages and correlations with biogeographic distribution

Abstract: Coastal marine ecosystems are highly vulnerable to anthropogenically introduced invasive species, in part because movement of organisms between diverse and widely separated habitats can occur rapidly. High rates of translocation, most notably via the ballast water of ocean-going ships (Carlton and Geller, 1993), allow potential invaders repeated opportunities to colonize coastal habitats. Indeed, the result of such continual introductions over the past century has been a rapid increase in the number of success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
100
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 42 publications
(54 reference statements)
10
100
0
Order By: Relevance
“…increased anthropogenic transport of nonnatives in driving this pattern (e.g. Stachowicz et al 2002, Fields et al 2006, Chown et al 2007, Scheibling & Gagnon 2009, Sorte et al 2010a, Willis et al 2010. There is recent evidence that phenologies of nonnative species have shifted concurrently with global increases in air and ocean temperatures (IPCC 2007a): events such as flowering (Willis et al 2010) and recruitment (Stachowicz et al 2002) are now occurring earlier in the year, in a direction that could give non-natives an advantage via priority effects (see Shulman et al 1983) if natives do not respond similarly.…”
Section: Introductionmentioning
confidence: 99%
“…increased anthropogenic transport of nonnatives in driving this pattern (e.g. Stachowicz et al 2002, Fields et al 2006, Chown et al 2007, Scheibling & Gagnon 2009, Sorte et al 2010a, Willis et al 2010. There is recent evidence that phenologies of nonnative species have shifted concurrently with global increases in air and ocean temperatures (IPCC 2007a): events such as flowering (Willis et al 2010) and recruitment (Stachowicz et al 2002) are now occurring earlier in the year, in a direction that could give non-natives an advantage via priority effects (see Shulman et al 1983) if natives do not respond similarly.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary data showed the possibility of differences in cMDH kinetic properties (Michaelis-Menten constant for cofactor NADH, K m NADH ) between mussels collected in this study as well (data not shown). Therefore, we investigated the possibility of a mutation in the cMDH genes at codon 114 (Fields et al 2006) that could underlie any potential differences. Codon 114 is known to differ between the 2 blue mussel congeners and M. californianus in a nonconservative amino acid substitution that is responsible for the differences found in substrate affinity (Fields et al 2006).…”
mentioning
confidence: 99%
“…Therefore, we investigated the possibility of a mutation in the cMDH genes at codon 114 (Fields et al 2006) that could underlie any potential differences. Codon 114 is known to differ between the 2 blue mussel congeners and M. californianus in a nonconservative amino acid substitution that is responsible for the differences found in substrate affinity (Fields et al 2006).We dissected a small piece of foot tissue from the same 10 acclimated mussels per site that were used for the enzyme activities. Genomic DNA was ex tracted from each sample using a NucleoSpin DNA extraction kit (BD Biosciences).…”
mentioning
confidence: 99%
“…However, these identified proteomic responses in As (V)-exposed mussel samples were completely different from those of As (III)-exposed group. Cytosolic malate dehydrogenase (cMDH) plays an important role in energy metabolism (Dahlhoff and Somero, 1993;Fields et al, 2006). The up-regulated cMDH in As (V)-exposed samples indicated that the energy metabolism was disturbed by As (V) in juvenile mussel.…”
Section: Effects Of As On the Proteome Of Juvenile Musselsmentioning
confidence: 99%